Zinc and cadmium adsorption from wastewater using hydroxyapatite synthesized from flue gas desulfurization waste - Kiziltas Demir, Sila; Tugrul, Nurcan (IWA PUBLISHING, 2021)
The purpose of this work is to produce an alternative cost-effective adsorbent to remove zinc and cadmium from wastewater using hydroxyapatite (HAP) synthesized with hydrothermal method from FGD (Flue gas desulfurization) waste generated by two different coal power plants. The effects of FGD type (Cayrhan and Orhaneli) and molar ratio (H3PO4/CaSO4) (0.6-4.79) on HAP synthesis were investigated. Afterwards effects of the adsorbent dose (1-2 g/L), heavy metal concentration (30, 40, 50 mg/L) and contact time (1, 2, 3, 4 h) on zinc and cadmium adsorption yield from synthetic wastewater using produced HAP were examined. FGD waste and synthesized FGD-HAP were characterized by X-Ray Diffraction (XRD), Fourier Transformed Infrared Spectroscopy (FT-IR), Scanning Electron Microscope (SEM) and Brunauer-Emmett-Teller (BET) instruments. The zinc and cadmium concentration was studied by Inductively coupled plasma atomic emission spectroscopy (ICP-AES). Maximum zinc adsorption capacity of the Cayrhan FGD-HAP was 49.97 and 49.99 mg/L, Orhaneli FGD-HAP was 49.96 and 49.99 mg/L, for 1 g/L and 2 g/L adsorbent dose respectively, for 50 mg/L heavy metal concentration and 4 h contact time. Maximum cadmium adsorption capacity of the Cayrhan FGD-HAP was 39.98 and 39.99 mg/L, Orhaneli FGD-HAP was 40 and 39.99 mg/L, for 1 g/L and 2 g/L adsorbent dose respectively, for 40 mg/L heavy metal concentration and 4 h contact time. Adsorption yields were calculated between 98.53 and 100%. The adsorption data were well explained by second order kinetic model and the Freundlich isotherm model fits the equilibrium data. The adsorption results demonstrated that FGD's waste is an effective source to synthesis HAP which is used as an adsorbent for zinc and cadmium removal from wastewater due to high adsorption capacity. HIGHLIGHTS An alternative FGD-HAP adsorbent was produced to remove Zn and Cd from wastewater. FGD waste generated by coal power plants was used for FGD-HAP synthesis. The heterogeneous and porous nature confirm that FGD-HAP is a successful adsorbent. The maximum removal efficiency of the FGD-HAP's was calculated between 98.53 and 100%. FGD waste pollution was eliminated and FGD waste was changed into valuable product.
Keywords: adsorption; cadmium; flue gas desulfurization; hydroxyapatite; waste; zinc; AQUEOUS-SOLUTION; IONS REMOVAL; SINGLE-METAL; HEAVY-METALS; FISH SCALE; GYPSUM; CONVERSION; COMPOSITE; EFFICIENT; PB(II); Engineering; Environmental Sciences & Ecology; Water Resources